(untitled) (Journal of Hama University, 2021)
The aim of the research is to determine the level of information awareness by using information sources on the Internet among graduate students at the Faculty of Education at the University of Damascus, and to achieve the goal of the research, the researcher prepared a questionnaire consisting of (31) items divided into three axes: information access skills, information evaluation skills, information use skills . The questionnaire was applied to a sample of (112) male and female students during the second semester of the academic year 2019-2020. The research reached the following results: The degree of information awareness among postgraduate students reached (3.241), which is a medium degree. - There are no statistically significant differences between the average scores of the sample members about their level of informational awareness using Internet information sources due to the gender variable. - There are statistically significant differences between the average scores of the sample members about their level of informational awareness using information sources on the Internet due to the scientific level variable in favor of doctoral students.